High-Temperature Superconductivity in Cuprates The Nonlinear Mechanism and Tunneling Measurements - Mourachkine, Andrei. (Fundamental Theories of Physics, An International Book Series on The Fundamental Theories of Physics: Their Clarification, Development and Application, 2002)
ỚSThe Frontiers of Knowhledge (to coin a phrase) are always on the move. - dayỚ"s discovery will tomorrow be part of the mental furniture of every research worker. By the end of next week it will be in every course of graduate lectures. Within the month there will be a clamour to have it in the undergraduate c- riculum. Next year, I do believe, it will seem so commonplace that it may be assumed to be known by every schoolboy. ỚSThe process of advancing the line of settlements, and cultivating and c- ilizing the new territory, takes place in stages. The original papers are p- lished, to the delight of their authors, and to the critical eyes of their readers. Review articles then provide crude sketch plans, elementary guides through the forests of the literature. Then come the monographs, exact surveys, mapping out the ground that has been won, adjusting claims for priority, putting each fact or theory into its placeỚ<U+00fd> (J. M. Ziman, Principles of the Theory of Solids (Cambridge University Press, 1972) p.v). The main purpose of the book is to present the mechanism of - perconductivity discovered in 1986 by J. G. Bednorz and K. A. M©ơller, and to discuss the physics of superconductors. The last chapter of the book presents analysis of tunneling measurements in cuprates. The book is - dressed to researchers and graduate students in all branches of exact sciences.